PENGARUH GERAKAN PBLHS TERHADAP KARAKTER PEDULI LINGKUNGAN SISWA DI SD NEGERI SAMIR - Mucholifah, Umi Hanik; Kadeni, Kadeni (INSPIRASI : JURNAL ILMU-ILMU SOSIAL, 2024)
Abstract Human character and interaction with the environment greatly affect the quality of the environment, so character education is key in instilling environmental awareness in the younger generation. This study aims to determine the effect of PBLHS Movement on the environmental care character of Samir State Elementary School students. This study uses a non-experimental quantitative approach with a correlational method and saturated sample technique, 98 students as a population. Data were collected through questionnaires that were compiled based on variable indicators. The results showed that PBLHS Movement had a positive and significant influence on students' environmental care character with a sig value. 0.000 0.05 and the tcount value is 6.296 ttable 1.6612. This finding supports the theory that the integration of the PBLHS Movement creates an effective synergy in shaping students' environmental care character. It is recommended that schools optimise this program and increase cooperation with parents and policy makers so that the results are even more optimal in improving the character of environmental care.Keywords: PBLHS Movement, Environmental Care Character